Pengaruh Penambahan Gliserol Terhadap Karakteristik Bioplastik Selulosa Batang Pisang/Kitosan - Lestari, Diani; Puspita, Indah; Kusmita, Tri (Jurnal Riset Fisika Indonesia, 2025)
The usage of plastics has brought negative impacts to the environment. Therefore, the development of bioplastics is required to solve the impact of the usage of plastics on the environment. In this study, bioplastics were developed based on banana stem cellulose, chitosan, and glycerol. The objective of this study was to determine the content of banana stems cellulose, functional groups, and the effect of glycerol addition on the thickness, mechanical properties, and degradation rate of bioplastics. The research was started by extracting cellulose from the stem of banana. Bioplastic synthesis was performed by adjusting the addition of glycerol. The bioplastics were examined for thickness, mechanical properties, functional groups, morphology, and degradation. The results indicated that the extracted banana stems produced cellulose with a concentration of 93%. It was identified to have cellulose functional groups in the form of O-H, C-H, and C-O. However, the addition of glycerol to bioplastics increased the thickness, elongation, and degradation rate, but decreased the tensile strength. Bioplastics with the best characteristics were produced by applying 3 mL glycerol with a thickness of 0,578 mm, tensile strength of 0,149 MPa, elongation of 2,7%, and completely degraded for 10 days.